An environmental watch system for the andean countries: El observatorio andino - Muñoz, Ángel G. (2010)
Observatorio Andino (OA) was established in 2008 by The Centro de Modelado Científico (CMC) in collaboration with Climate information applied to agricultural risk management in the Andean countries (CIIFEN). The OA main goal is to provide a collaborative network that ultimately increases the efficiency of the decision-making processes, especially in terms of getting more accurate forecasts and exchanging experiences on data, information, and scientific products, all of which is done with a standardized methodology and a Web-sharing service. The Observatorio Andino follows a three level hierarchical model execution flux, with the same approach for both short-term and seasonal products. In order to facilitate the validation process, a spatial map for each time slice of interest involving the differences and/or the anomaly correlations between model output and observations, is generated. The OA makes extensive use of its wiki, webinars, and video conferences for standardizing the methodologies.